Evaluation of expelled soybean meal in swine finishing diets - J L Lauren; Robert D Goodband; Michael D Tokach; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1992)
Thirty crossbred fmishing gilts (initial weight = 150 lb) were used to evaluate the effects of feeding expelled soybean meal (41% analyzed CP) or conventionally extracted soybean meal (46.5% analyzed CP) on growth performance. Gilts were fed a control diet containing conventionally processed soybean meal or diets containing expelled soybean meal formulated to replace conventionally extracted soybean meal on either a guaranteed protein basis or an analyzed protein basis. Thus, the effects of possible variation in the protein content and quality of expelled soybean meal as a result of expeller processing could be established. Gilts fed either diet containing expelled soybean meal had decreased average daily gain (ADG) and average daily feed intake (ADFI) and tended to have poorer feed efficiency (FIG) than gilts fed conventionally processed soybean meal. Although not statistically different, gilts fed the expelled soybean meal diet formulated on a guaranteed protein content basis tended to have poorer ADG than those fed the expelled soybean meal formulated on an analyzed protein content. These results suggest that improper processing and the potential variation present in expelled soybean meal used in this experiment resulted in decreased pig performance.; Swine Day, Manhattan, KS, November 19, 1992
Keywords: Swine day; 1992; Kansas Agricultural Experiment Station contribution; no. 93-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 667; Swine; G-F; Performance; SBM; Process